STUDI KASUS DIABETES SELF MANAGEMENT EDUCATION SEBAGAI KONTROL GLUKOSA DARAH PASIEN DIABETES MELITUS DI RSUD TARAKAN - Devi Saraswati, Cicilia; Sukarno, Anita; Asmirajanti, Mira; Ariyanti, Rika Mustika (Alauddin Scientific Journal of Nursing, 2022)
Background: Diabetes Mellitus (DM) is a metabolic disorder disease characterized by an increase in blood sugar levels (hyperglycemia) caused by a lack of insulin. One of them is with Diabetes Self-Management Education (DSME) to optimize metabolic control, prevent complications, and improve the patient’s quality of life. The purpose of this study was to analyze and provide an overview of nursing care with Diabetes Self-Management Education (DSME) in patients with diabetes mellitus. Methods: the research method used is a case study with exploratory descriptive analysis. The results of this study are the characteristics of patients who become respondents are 3 subjects with diabetes mellitus in the elderly category (over 45 years). The gender of the respondents were 2 female patients and 1 male patient who had an elementary education level in both patients and 1 patient had a high school education level. Nursing problems that arise in patients with diabetes mellitus are the risk of blood sugar instability. The application of nursing care with Diabetes Self-Management Education (DSME) in nursing interventions helps patients and families understand and understand how to check blood sugar and also administer insulin independently as a form of blood sugar control management to prevent complications. The patient’s blood sugar control also decreased. Conclusion: Diabetes Self-Management Education (DSME) helps patients to control blood glucose independently. Recommendation: The application of Diabetes Self-Management Education (DSME) can be a nursing intervention in overcoming the management of independent blood glucose control in patients with diabetes mellitus to prevent complications. Keywords: Blood Glucose, Diabetes Mellitus, Diabetes Self-Management Education (DSME)